The Secure online business handbook e-commerce, IT functionality & business continuity - Reuvid, Jonathan (Gale virtual reference library, 2005)
Practical guide for managers in developing and implementing appropriate strategies for online risk management. Contributions draw on a wide range of expertise and know-how, both in IT and in other disciplines such as the law, insurance, accounting and consulting.